Development of a multicomponent intervention to increase parental vaccine confidence and young people's access to the universal HPV vaccination programme in England: protocol for a co-design study. Issue 4 (6th April 2022) - Fisher, Harriet; Chantler, Tracey; Denford, Sarah; Finn, Adam; Hickman, Matthew; Mounier-Jack, Sandra; Roderick, Marion; Tucker, Leanne; Yates, Julie; Audrey, Suzanne
Abstract : Introduction: Persistent infection with HPV can result in cancers affecting men and, especially, women. Lower uptake exists by area and different population groups. Increasing parental confidence about, and adolescent access to, the universal HPV vaccination programme may help reduce inequalities in uptake. However, the evidence-base for interventions to address uptake for schools-based HPV vaccination programmes is currently lacking. This study protocol outlines how a multicomponent intervention to address this evidence gap will be codesigned with parents. Methods and analysis: The proposed research will be undertaken in localities covered by two immunisation teams in London and the south-west of England. The 'person-based approach' to intervention development will be followed. In the first phase, an exploratory qualitative study will be undertaken with key stakeholders (n=8) and parents (n=40) who did not provide consent for their adolescent child to be vaccinated. During the interviews, parents' views on ways to improve parental confidence about, and adolescents' access to, HPV vaccination will be sought. The findings will be used to inform the co-design of a preliminary plan for a targeted, multicomponent intervention. In the second phase, at least two parent working groups (n=8) will be convened and will work with creative designers to co-design communication materials aimed at increasing parents' confidence in vaccination. At least two workshops with each parent group will be organised to obtain feedback on the intervention plan and communication materials to ensure they are fit for purpose. These findings will inform a protocol for a future study to test the effectiveness of the intervention at increasing HPV vaccination uptake. Ethics and dissemination: The National Health Services Research Ethics Service and London School of Hygiene & Tropical Medicine Observational / Interventions Research Ethics Committee provided approvals for the study (reference 22/SW/0003 & 26902, respectively). We will work with parent advisory groups to inform our dissemination strategy and co-present our findings (eg, at community events or through social media). We will disseminate our findings with academics and healthcare professionals through webinars and academic conferences, as well as peer-reviewed publications.